Decentralising Climate Governance in the Global South: Lessons from Itezhi-Tezhi and the Kafue Wetlands, Zambia - Ndambwa, Biggie Joe; Moonga, Given (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
This article discusses the challenges of decentralising climate governance in the Global South in the context of intensifying climate change. Using qualitative methods of data collection and analysis, we interviewed a total of 112 participants who participated in the study, including traditional leaders, ward councillors, subject-matter experts, government officials and members of the public who took part in focus group discussions. Our results show that devolution, delegation, deconcentration and privatisation have been used as strategies for decentralising climate action in the Itezhi-Tezhi District. However, these methods of decentralisation are affected by several factors, including unclear rules for elected and appointed leaders, which influence the devolution of decision-making responsibilities at the local government level. Regarding delegation, decentralising climate governance is affected by inadequate public participation, particularly in the design and execution of climate initiatives in the Kafue wetlands. Furthermore, this article shows that deconcentration is likely to affect climate governance because the national government has not deconcentrated the units for climate governance from the line ministry to the local authority. Privatisation, which has been an effective way of decentralising climate governance in the Kafue wetlands, has also been problematic due to inadequate community participation. These challenges and opportunities serve as lessons for building resilience in effective decentralised climate governance in the Kafue wetlands. This article adds to the ongoing discourse on the efficacy of decentralising climate governance in the Global South and offers valuable insights for future research in this genre of academic inquiry in Sub-Saharan Africa.